Evaluation of diagnostic measurements in patients with non-specific complaints: A secondary analysis after implementation of a care-pathway in the emergency department - M. G. A. M. van der Velde; M. A. C. Jansen; H. R. Haak; M. N. T. Kremers (PLoS ONE, 2025)
Background Older patients presenting with nonspecific complaints (NSC) in the Emergency Department (ED) pose diagnostic challenges. The lack of clear symptoms leads to high misdiagnosis rates, extended hospital stays, and functional impairment. However, limited research exists on diagnostic test utilization for this population. Methods A secondary analysis was conducted on data from 399 older patients (aged 70+) at two hospitals in the Netherlands. These patients presented with NSC and were assessed using a standardized care-pathway that included diagnostic tests such as blood tests, ECGs, chest X-rays, and bladder ultrasounds. Data from a control group (164 patients) and an intervention group (235 patients) were compared, focusing on adherence to the diagnostic pathway, test frequency, and clinical outcomes. Results The intervention group showed significantly greater use of several diagnostic tests compared to the control group, specifically calcium, TSH, glucose, ALAT, ECGs, chest X-rays, and bladder ultrasounds. Notably, abnormal findings were relatively low across tests, particularly for ALAT, TSH and calcium. Urinalysis, chest X-rays and ECGs were used more frequently and identified clinically significant findings. Head CT scans were used more frequently in the intervention group, though not statistically significant. Conclusion We recommend a standardized laboratory work-up for patients presenting with NSC. There is no justification for the routine use of ALAT, TSH and calcium measurements. We also recommend to incorporate bladder scans into routine care, and continuing the standardized use of ECGs, chest X-rays and urinalysis. Head CT scans, on the other hand, should be based on individualized clinical decisions. Trial number: Dutch Trial register, number NL8960.